#Engagement: use of Twitter chats to construct nominal participatory spaces during health crises. Issue 4 (3rd April 2018) - Young, Rachel; Tully, Melissa; Dalrymple, Kajsa E.
ABSTRACT: Although Twitter chats and other forms of social media engagement events are idealized in the literature as opportunities for dialogic communication between organizations and individuals, less is known about how engagement is operationalized within these spaces. Using textual and content analysis, we conducted two studies to explore how health organizations engage with the public via Twitter chats during the Ebola and Zika outbreaks. In official records of Ebola chats, the organization addressed both hostile and neutral public questions that pressed for specification of disease characteristics and protocol. However, in a content analysis of all public tweets sent during a later Zika chat, we found that questions were privileged, and other tweet forms and themes were excluded from the participatory space. Specifically, public comments demonstrating expertise or extending the topic of the chat were not addressed by the organization. Our analysis provides insight into the implicit rules governing how organizations engage with the public online during a rapidly evolving health crisis. We argue that the question–response dyad is a form of ideal communication that suggests engagement but maintains organizational expertise.